Understanding Islam : contemporary discourse - Kamaruzaman, Kamar Oniah (Saba Islamic Media, 2009)
A comprehensive exposition of Islam written for contemporary readership, covering fundamentals of Islam and subjects of contemporary concerns. Topics include concepts of din (religion)and faith (submission), Arkan al-Islam (pillars of Islam), Arkan al-Iman (pillars of iman), social institutions and contemporary issues with Islamic perspective.